Chronic hepatitis B prognostic markers other than pre-treatment viral load predicted composite treatment outcome - Aung, Myo Nyein; Leowattana, Wattana; Win, Khine Nwe; Tangpukdee, Noppadon; Muangnoicharoen, Sant (The Journal of Infection in Developing Countries, 2013)
Introduction: Chronic hepatitis B (CHB) is a globally common infectious disease. Its clinical course is complicated. In Southeast Asia, nucleos(t)ide analogues (NA) are commonly used drugs for CHB treatment. Composite treatment outcome has often been used in CHB clinical practice, but rarely predicted epidemiologically. This study aimed to compare the composite treatment outcome between CHB patients with low and high treatment-naïve viral load, and to identify its predictors Methodology: This retrospective cohort study followed up 95 CHB patients on NA treatment for a year. Composite treatment outcome was defined as undetectable HBV DNA level, ALT normalization and, HBeAg clearance in the case of HBeAg-positive patients. Multinomial logistic regression analysis was applied to analyze the significant treatment response predictors. Results: Complete composite treatment outcome was achieved by 52% of CHB patients with an initial viral load < 6.5 log 10 copies /ml, but 31% of those had an initial viral load ≥ log 6.5 log 10 copies /ml. Outcome was predicted by HBeAg negativity (adjusted relative risk ratio, aRRR = 11.1, 95 % confidence interval, CI 3-41.3) and ALT normalization within the sixth month of therapy (aRRR = 6.7, CI 1.8-24.9). An elevation of ALT to more than 1.5 times the normal value (40 IU/ml) can lead to an incomplete response on NA therapy (aRRR = 6.2, CI 1.5-26.6.) Conclusion: Routine clinical markers other than pre-treatment viral load predicted composite CHB outcome on NA Therapy.